Only yesterday : a novel - Agnon, Shmuel Yosef, 1887-1970 (Princeton classics, 2018)
Tells a seemingly simple tale about a man who immigrates to Palestine with the Second Aliya -- the several hundred idealists who returned between 1904 and 1914 to work the Hebrew soil as in Biblical times and revive Hebrew culture. Only Yesterday quickly became recognized as a monumental work of world literature, but not only for its vivid historical reckon of Israel's founding society. This epic novel also engages the reader in a fascinating network of meanings, contradictions, and paradoxes all leading to the question, what, if anything, controls human existence?